2018
DOI: 10.9755/ejfa.2017.v29.i12.1567
|View full text |Cite
|
Sign up to set email alerts
|

Response of winter wheat grain yield and water use efficiency to deficit irrigation in the North China Plain

Abstract: Water resources in the North China Plain (NCP) are limited, so it’s in urgent need to optimize deficit by irrigation for sustainable winter wheat production in this area. Winter wheat grain yield (GY), contribution of dry matter (DM) remobilization to GY (CDMRG), and water use efficiency (WUE) were investigated in NCP. Compared with non-irrigation treatment, irrigated with 60 mm each at the winter wheat jointing stage (JS) and heading stage (HS) achieved reasonable winter wheat GY and WUE. Compared with irriga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…Complex crop responses to water stress have continually been a research focus of deficit irrigation (Andarzian et al., ; Iqbal et al., ; Mkhabela & Bullock, ; Steduto, Hsiao, Raes, & Fereres, ; Toumi et al., ). Many studies have analyzed the relationships between crop growth, ET, and RWU (Goosheh, Pazira, Gholami, Andarzian, & Panahpour, ; Han et al., ; Jha et al., ), while others have studied crop growth and ET under deficit irrigation (Salemi et al., ; Yu, Zeng, Su, Cai, & Zheng, ). Andarzian et al.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Complex crop responses to water stress have continually been a research focus of deficit irrigation (Andarzian et al., ; Iqbal et al., ; Mkhabela & Bullock, ; Steduto, Hsiao, Raes, & Fereres, ; Toumi et al., ). Many studies have analyzed the relationships between crop growth, ET, and RWU (Goosheh, Pazira, Gholami, Andarzian, & Panahpour, ; Han et al., ; Jha et al., ), while others have studied crop growth and ET under deficit irrigation (Salemi et al., ; Yu, Zeng, Su, Cai, & Zheng, ). Andarzian et al.…”
Section: Introductionmentioning
confidence: 99%
“…Serious water shortages force people to implement deficit irrigation. Researchers have reported that this irrigation method can effectively improve water use efficiency without many adverse effects on yield (Han, Ren, Gao, Yan, & Li, 2017;Li, Bian, Liu, Ma, & Liu, 2015).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…At present, several water‐saving irrigation technologies have made good progress and have been popularized in northwest China. These include deficit irrigation, drip irrigation, sprinkler irrigation, and film‐mulched irrigation . Deficit irrigation may be the appropriate choice to reduce irrigation water amounts and improve crop water efficiency .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to full irrigation, deficit irrigation can reduce irrigation depth by 20–50%, thus resulting in greater productivity of chili pepper plants in northwest China . Moreover, deficit irrigation can be applied easily in the fields and has been widely implemented in recent years . Previous research mainly focused on the effects of deficit irrigation on winter wheat yield and quality, and a few studies have analyzed the effects of deficit irrigation on soil CO 2 emissions from winter wheat fields.…”
Section: Introductionmentioning
confidence: 99%